Exploring health seeking behaviour among incidentally diagnosed HIV cases in Rawalpindi, Pakistan: A qualitative perspective - Rathore, Mommana Ali; Rashid , Zubaida; Khushk, Imdad; Mashhadi , Syed Fawad; Rathore, Muhammad Ali; Barnes, Sarah (Journal of the Pakistan Medical Association, 2022)
Objective: To identify the determinants of health-seeking behaviour among incidentally diagnosed cases of HIV and to explore the patterns of care seeking behaviour among these HIV infected persons. Method: The qualitative study based on the grounded theory was conducted from February to September 2019 at the Armed Forces Institute of Transfusion, Rawalpindi, Pakistan, and comprised incidentally diagnosed new cases of human immunodeficiency virus. Data was collected using in-depth interviews to understand how local environments and settings impact healthcare-seeking behaviour. Data was analysed using the constant comparison method. Results: Of the 12 patients, 10(83.3%) were male, 1(8.3%) female and 1(8.3%) transgender. The mean age of the sample was 31+5 years. Of the total, 10(83.3%) patients were receiving free antiretroviral treatment from government hospitals in Rawalpindi/Islamabad, while 2 (16.7%) opted for some alternative form of healthcare. Ten (80%) were married and were carrying the diagnosis for >6 months. Processing of human immunodeficiency virus status, value placed in one’s own health, experiences with healthcare provider and medication-related factors were the main themes that emerged from the data. Better counselling services, free-of-cost medication, positive patient-provider relationship and social support were the key players, while non-disclosure due to fear of stigma and beliefs about the disease were the main stumbling blocks. Conclusion: Value placed in one’s own healthcare and thus the need for healthcare services, regardless of social norms, cultural reservations and personal beliefs, was the most important factor affecting the healthcare-seeking behaviour of human immunodeficiency virus patients. Key Words: Grounded theory, Health-seeking behaviour, Human immunodeficiency virus, HIV.